SUITABILITY OF KUUSIVAARA, SODANKYLÄ, CENTRAL FINNISH LAPLAND FOR HOSTING MINING INFRASTRUCTURE BASED ON ITS STRATIGRAPHY - Valkama, Markus (Helsingin yliopisto, 2023)
AA Sakatti Mining Oy is planning on utilising the Cu-Ni-PGE deposit discovered in 2009 in Sodankylä, central Finnish Lapland. Sediments of Kuusivaara hill and Porokodanjänkä mire were studied to find out their feasibility in regards to hosting mining infrastructure. Six test pits were excavated, fourteen soil samples analysed, and fifteen kilometres of ground penetrating radar profile was acquired. A GIS-based bedrock elevation model, a sediment thickness model and a peat thickness model were created. The bedrock and sediment thickness models were supplemented with data gathered in other relevant studies in the area to extend these models to cover Kenttäaapa mire north of Kuusivaara. Local stratigraphy corresponds with typical stratigraphy of central Finnish Lapland. Two till beds with occasional, thin interlayers of sand blanket the central and eastern parts of the area. Their hydraulic conductivity is poor. Till thickness ranges from two to six metres. The flanks of the river Kitinen are covered with thick and permeable fluvial sediments. Peat thickness at Porokodanjänkä mire ranges from less than 0.5 metres to 5.4 metres. Mean sediment thickness, including peat thickness, is 5.5 metres. The mean peat thickness under Porokodanjänkä is 1.3 metres. The bedrock surface, especially under Porokodanjänkä mire shows frequent weathering. This is a typical phenomenon under the low-erosion regime of the ice divide zone. Maximum weathering depths were not clarified by this study. The study area is mostly suitable for hosting mining infrastructure. Except under the old channel of river Kitinen, sedimentary units demonstrate poor hydraulic conductivity. There are no significant acquifers in the area. Full extent and depth of weathered bedrock must however be mapped before initiating construction of mining infrastructure. Weathered and fractured bedrock is significantly more permeable than crystalline bedrock. Such units must therefore be identified to understand local hydrology. AA Sakatti Mining OY suunnittelee vuonna ...